Teacher Performance and Student Fitness: Is there a Significant Relationship? - Bella Shasi Saraswara; Ali Maksum; Advendi Kristiyandaru; Muhammad Labib Siena Ar Rasyid (Universitas Riau, 2024)
This research aims to reveal the level of PF of students in ten JHS based on the results of PE teachers' performance based on four competencies. An Ex Post Facto approach was used in this survey research. The instrument to see the performance of PE teachers is to use a questionnaire. Meanwhile, to measure students' PF, the test used is the bleep test. The principal, deputy principal for public relations, deputy principal for curriculum, and one student in class VIII (eight) whose physical fitness data was taken randomly from each school were used as samples in this study. The results of this research include: (1) the performance of JHS PE teachers in Pekanbaru City has met expectations because the four competencies are in the very good category, where personality competency has the highest percentage, (2) Lack of PA inside and outside school will causes low PF of students (Vo2Max), (3) From the results of the regression test which shows a figure of 14.3%, it shows that the high quality of PE teachers' performance does not have a direct impact on students' PF. The conclusion of this research is that the competence of PE teachers does not have a significant impact on students' PF levels because there are other factors that influence it, such as the level of active participation of students inside and outside school. These findings recommend, among other things: (1) the need for consistency in the quality of PE teachers and the professionalism of teachers in schools, (2) the need to maintain the quality of students' PF to improve the quality of life, (3) the need to determine or select PE materials that are adapted to the characteristics of children so that students can be more active in the learning process so that the goals of PE are achieved.